MENINGKATKAN AKTIVITAS DAN HASIL BELAJAR GEOGRAFI PADA POKOK BAHASAN POTENSI GEOGRAFI INDONESIA MENGGUNAKAN MODEL PEMBELAJARAN KOOPERATIF TIME TOKEN DI KELAS XI IPS 4 SMA NEGERI 2 PEKANBARU: (Improving Activity And Learning Outcome of Geography subject wih the Topic Indonesian Geography Potency Using Cooperative Learning Model Time Token XI IPS 4 SMA Negeri 2 Pekanbaru) - Afnidaleni Afnidaleni (Perspektif Pendidikan dan Keguruan, 2017)
ABSTRACTLearning is an active process in gaining experience or new knowledge that causes behavioralchanges. Wena said a teacher must be able to set, choose and apply a learning strategyappropriately so as to solve the existing learning problems and ultimately can achieve thecompetence or learning objectives optimally.Teachers are required to perform their dutiesprofessionally, able to understand and have adequate skills in developing effective, creativeand fun learning models. Cooperative learning model is a model of learning where learnerslearn and work in small groups with different levels of ability. One alternative learning modelthat is expected to enable learners is the cooperative learning model Time Token.The TimeToken cooperative learning model is a learning model that aims to have each member of thediscussion group get a chance to contribute in conveying their opinions, as well as to preventlearners from dominating silent conversations and learners. Arends (2008) explains that TimeToken is a cooperative learning model used to develop students' participation skills. In thiscase Time Token helps the distribution of uneven participation in learners. And also one smallexample of the application of democratic learning in schools. Democratic learning process isa learning process that puts learners as subjects and can affect the learner activities that canthen support the improvement of learning achievement.The implementation of Time Tokencooperative learning model is expected to be able to overcome the problems with thecondition of learners in less active classes during the learning process and group discussionand can reduce the students dominating the conversation as well as the social interaction withother friends that can spur the formation of new responses / opinions and enrich Intellectuallearners, so that all learners can participate actively so that learners understanding betterand lead to increase learning achievement learners. Based on the results obtained the valueof the first cycle, the second cycle and the third cycle in a row (77.69 %), (79.23%) and(84.61%).